Analisis kinerja variasi jenis dan ketebalan isolator pada dinding ruang mesin pengering kemiri - Zaky Abdul Aziz; Mietra Anggara (TURBO [Tulisan Riset Berbasis Online], 2022)
Candlenut (Aleurites moluccana Willd) has various benefits and has high economic value. Candlenut seeds are widely used by the community as cooking spices, for cosmetic purposes, until the oil is taken for industrial purposes. So far, the process of processing candlenut seeds carried out by candlenut entrepreneurs in Batulanteh District, Batu Dulang Village, Sumbawa Regency is still simple, namely by drying under direct sunlight and using a solar dryer. This causes the drying process of candlenut seeds to take quite a long time. To increase the drying time of candlenut seeds, further research is needed on the development of a candlenut drying machine. This research is a study on the development of a candlenut drying machine by comparing variations in the type and thickness of the insulator on the wall surface of the candlenut drying room. The results of the study with a time of 60 minutes with a temperature of 80°C and a thickness of 6 mm showed that the use of aluminum foil, glasswool, and stryfoam insulators can accelerate the evaporation of hazelnut moisture content with values of 3%, 2%, and 2%, respectively.